Study on transfer and persistence of fibers: A systematic review - Manashree Mane; G Devika (Wolters Kluwer Medknow Publications, 2022)
Fiber evidence has played a crucial role in ascertaining various characteristics and has aided in providing evidential value to the fiber evidence as well as reconstructing events during crime scene investigation. Although fibers are transferred easily at the crime scene and various methods of interpretation exist, it is challenging to get a fiber match. The present study aims to provide a systematic review of the role of fiber as trace evidence. It explores the fiber population, transfer and persistence of fibers, fiber shedability and recovery, effect of laundry on fibers, stabbing events, the resistance of fabric against weapon's penetration, the behavior of fabric upon ballistic impact, and various analytical techniques of fiber examination. The study approaches to evaluate the significances and uncertainties of the recovered fiber evidence.